SARS-CoV-2 spike protein increases angiotensin converting enzyme-2 expression and promotes an increase in glucose uptake in endothelial cells - Mariana F. Campos; Larissa E. C. Constant; Larissa E. C. Constant; Douglas E. Teixeira; Rodrigo P. Silva-Aguiar; Patrícia R. M. Rocco; Ronaldo Mohana-Borges; Gilda G. Leitão; Celso Caruso-Neves; Suzana G. Leitão; Diego Allonso (Acta Virologica, 2024)
Coronavirus Disease 2019 (COVID-19) pandemic led to 7 million deaths and more than 770 million confirmed cases worldwide. The Spike glycoprotein (SP) is responsible for recognizing and binding to angiotensin converting enzyme-2 (ACE-2) in the host cell membrane and seems to modulate host cellular signaling pathways. Here, we investigate the effects of SP (stabilized in prefusion conformation) in human umbilical vein endothelial cells (HUVEC-C) lineage on the ACE-2 expression profile and in cell glucose metabolism. Our data indicate that SP binds to ACE-2, is internalized by HUVEC-C cells, and positively modulates ACE-2 expression. In addition, SP alone induces a transient increase in glucose uptake and a decrease in lactate production, characterizing itself as a metabolic regulating protein. The present study is the first to demonstrate that SP induces a slight change in cell metabolism, promotes the overexpression of ACE-2 and its increased availability in the membrane of endothelial cells in a time-dependent fashion.